Rewriting dialectal Arabic prehistory the ancient Egyptian lexical evidence - Borg, Alexander (Brill, 2021)
"Deploying a bottom up instead of the conventional top down approach, and drawing extensively on both literary and dialectal Arabic lexical sources, the present glossary proposes and validates the contention of a prehistoric symbiosis transpiring between Ancient Egyptian and Arabic two and a half millennia before the advent of Islam. Its empirical rationale and methodological basis rest firmly on these venerable idioms' rich textual documentation, yielding the language historian an ample etymological database enriched-in the case of Arabic-with a virtually unlimited corpus drawing on the living speech of some 300 million speakers across the Near East and Africa. The muster provided here comprises over 800 lexemes and reveals, for the first time in longue durée research on Afroasiatic, striking unsuspected commonalities linking Old Egyptian to Yemeni Arabic"--
Keywords: Ägyptisch; Dialektologie; Arabisch; Egyptian language / Glossaries, vocabularies, etc / Arabic; Arabic language / Etymology / History; Arabic language / Dialects / Yemen; Arabe (Langue) / Étymologie / Histoire; Arabic language / Dialects; Arabic language / Etymology; Yemen (Republic); History